2000
DOI: 10.1002/1097-4628(20001010)78:2<355::aid-app150>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the reactivity of phenolic compounds with formaldehyde under basic conditions: Anab initio study

Abstract: A method is needed to predict which compounds, from the many alternative phenolic compounds, might be best for making polymeric phenolic systems. Kinetic data for the reaction of a series of phenolic compounds with formaldehyde using a base catalysis are available in the literature. Semiempirical calculations, using RHF/PM3, and ab initio calculations, using RHF/6‐31G, RHF/6‐31+G, and B3LYP/6‐311+G(2d,p), were performed on the series of phenolic compounds to determine their relative reactivities. Atomic charge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…10.6 and 11.6, respectively [55]. This suggests that these disubstituted phenols should be more reactive towards electrophilic substitution than the tyrosine phenol [56,57]. For instance, it can be expected that thymol and 2,4-ditert-butylphenol would react faster with the imine electrophile than the phenol moiety of tyrosine and limit the self-condensation of tyrosine.…”
Section: L1 L2mentioning
confidence: 99%
“…10.6 and 11.6, respectively [55]. This suggests that these disubstituted phenols should be more reactive towards electrophilic substitution than the tyrosine phenol [56,57]. For instance, it can be expected that thymol and 2,4-ditert-butylphenol would react faster with the imine electrophile than the phenol moiety of tyrosine and limit the self-condensation of tyrosine.…”
Section: L1 L2mentioning
confidence: 99%
“…Thus, to remove the harmful chlorinated organic compounds efficiently, including CPs which are the by-products of industrial processes, a variety of experimental [3][4][5][6][7] and theoretical [8][9][10][11][12][13][14][15][16] studies are being carried out. To evaluate the photo degradation characteristics of chlorinated organic compounds, several studies using the density functional theory (DFT) method have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, there have merely been studies predicting the reaction of formaldehyde with alkaline phenol among phenol compounds based on the calculation of the atomic charges. [12][13][14] Thus, to understand the ·OH substitution reaction of phenols, CPs and CNB at the molecular level, it is important to predict what products are made in radical reaction by Fenton or ozone. A deep comprehension of the ·OH reaction mechanism of these harmful chlorinated organic compounds is also important.…”
Section: Introductionmentioning
confidence: 99%